The Sociological Research on LGBT population in Italy - Zanola, Elisa (Italian Sociological Review, 2014)
In this paper, five of the most important books written by Italian Sociologists on LGBT population in Italy are reviewed. The specificity of the Italian context, which in large part is also due the delay of the Italian debate on LGBT issues, is also analysed. Despite this, Italian research has its own particular characteristics and its own wealth, here considered, recognizing at the same time the limits of a field (on Gender, Gay and Lesbian Studies) which has only recently begun to enter Sociological Studies in Italy.